The influence of using wordwall media on students' conceptual understanding of composition function material - Desi Natalia Naibaho; Nicky Dwi Puspaningtyas (Fakultas Tarbiyah dan Ilmu Keguran IAIN Metro, 2026)
The main objective of using Wordwall learning media is to facilitate students in understanding mathematical concepts, particularly in composition function material, through interactive and engaging activities. The method used is a quasi-experiment with a Nonequivalent Control Group Pretest-Posttest Design involving two grades of XI high school, namely the experimental class that learned using WordWall media and the control class that learned conventionally. Data were obtained through essay tests that had been tested for validity, reliability, difficulty level, and discriminatory power, then analyzed using the Liliefors normality test, Bartlett's homogeneity test, and the Independent Sample t-test with the help of SPSS. The results showed that the data were normally distributed and homogeneous, and the significance value (Sig.) <0.05, which indicates a significant difference between the understanding of the concept in the experimental and control classes. In addition, more than 75% of students in the experimental class achieved the Minimum Completion Criteria (KKM), so it can be concluded that the use of WordWall media is effective in improving the understanding of mathematical concepts.